Potential contribution of lysed bacterial cells to phosphorus solubilisation in two rewetted Australian pasture soils - Turner, Benjamin L; Driessen, Jennifer P; Haygarth, Philip M; Mckelvie, Ian D (Soil biology & biochemistry, 2003)
Soil drying renders considerable amounts of phosphorus soluble upon rewetting, which may be partly derived from lysed microbial cells. Using direct bacterial cell counting in water and tetra-sodium pyrophosphate extracts of two Australian pasture soils, we found that almost all extractable cells were lysed following the rewetting of dry soils. The amounts of phosphorus in the lysed cells corresponded closely to the increases in water-extractable phosphorus following soil drying, suggesting that bacterial cell lysis is a major source of the released phosphorus.